Decolonizing Buddhist Authority: Religious Nationalism and State-Sanctioned Violence in Myanmar - Muhammad Maulidan (Journal of Religion and Decoloniality, 2025)
This paper discusses the involvement of religious authorities in the reproduction of violence against the Rohingya community in Myanmar. Using Johan Galtung's triangle of violence theory, this paper shows that violence does not only appear in physical forms, but is also institutionalized through state structures and normalized by religious narratives. This study traces how the 2017 military operations, the 1982 Citizenship Law, and the emergence of Buddhist nationalist movements such as Ma Ba Tha and the 969 Movement are part of a systematic process that legitimizes violence in the name of protecting religion and the nation. Rather than viewing Buddhism as a peaceful doctrine or its opposite, this paper highlights how religion is used as a tool of legitimation in postcolonial state-building projects. Religion serves to draw lines of identity between “us” and “them,” thereby enabling the state to exclude groups deemed incompatible with an exclusive national identity. Within Galtung's framework, direct violence against the Rohingya cannot be separated from structural violence that institutionalizes exclusion, and cultural violence that makes it appear legitimate. These three forms of violence reinforce each other and demonstrate that violence is not merely an aberration, but rather part of a planned and sustained logic of power. This article contributes to studies on religious nationalism, state violence, and the role of sacred authority in exclusionary politics